Juventudes e expressividades musicais no espaço escolar do Alto Sertão de Alagoas - Silva, Isabel Cristina Oliveira da (2018)
This dissertation is the result of a quantitative-qualitative, exploratory and descriptive research, which aims to understand how the relation youth, school and music works in Delmiro Gouveia, a city at the backwoods of Alagoas. We took as sample 116 young enrolled in the 3rd year of high school of Public School Luiz Augusto Azevedo de Menezes, who were interviewed through questionnaires, semi-structured interview and free observation of school routine. It was noted that these young build their identities through deconstruction of classic theory about the rural, denoting representations and lifestyle of their musical tastes, enlarged by virtual and concrete interactions. We found a diverse youth profile, with minimal age/series mismatch. The students are residents of village, district and local seat with their parents or relatives, and some are workers. It is a youth of very eclectic musical taste and some take part in musical performances in a most vehemently way with participation in religious choir and city orchestra. During the research, it was verified a school-youth-music relation, surrounded by tension and rules. At the same time it was noticed a somewhat sensitive look of the teachers and school management to the juvenile expressiveness. The reflections were guided by comprehensive incursions of Sociology and Education, with a humane and conscientious analysis of the data, and an understanding that the same research problem may present diverse interpretations depending on theoretical and methodological field. We conclude that this work contributes to the expansion of context and themes of research related to rural youth, and, also, to repeal pragmatic conceptions which states that school trajectories, cultural expressiveness, and life projects of rural youth are defined by destiny of class or local origins.